FACTORS INFLUENCING ADHERENCE TO THERAPY IN HIV-POSITIVE DRUG-DEPENDENT PATIENTS - E. P. Stan’ko; S. A. Igumnov (Медицинский вестник Юга России, 2013)
Purpose: To identify factors influencing adherence to therapy in HIV-positive injecting drug users and offer a basic conceptual model aimed at improving adherence.Materials and Methods: Using the method of anonymous questionnaire to assess adherence to therapy in HIV-positive injecting drug users.Results: the factors that affect adherence to treatment, the study of which is necessary for the development of a conceptual model, which is the basis for the planned activities aimed at improving adherence to treatment in HIV-positive drug users.Summary: The individual and personal, health, social and organizational factors are involved in the structure of the conceptual model.